An intelligent multimodal framework for identifying children with autism spectrum disorder - Chen, Jingying; Liao, Mengyi; Wang, Guangshuai; Chen, Chang (Zielona Góra: Uniwersytet Zielonogórski)
Early identification can significantly improve the prognosis of children with autism spectrum disorder (ASD). Yet existing identification methods are costly, time consuming, and dependent on the manual judgment of specialists. In this study, we present a multimodal framework that fuses data on a child`s eye fixation, facial expression, and cognitive level to automatically identify children with ASD, to improve the identification efficiency and reduce costs.
Keywords: autism spectrum disorder; eye fixation; facial expression; cognitive level; improved random forest